Outcomes of Recurrent Head and Neck Cutaneous Squamous Cell Carcinoma - Nichole R. Dean; Larissa Sweeny; J. Scott Magnuson; William R. Carroll; Daniel Robinson; Renee A. Desmond; Eben L. Rosenthal (Journal of Skin Cancer)
Recurrent, advanced stage cutaneous squamous cell carcinoma (cSCC) is uncommon with limited publications on patient outcomes. A retrospective study including patients who underwent surgical resection for recurrent, advanced stage cSCC of the head and neck was performed (n=72). Data regarding tumor site, stage, treatment, parotid involvement, perineural invasion, positive margins, metastasis, and disease-free survival was analyzed. The majority of patients were male (85%) and presented with recurrent stage III (89%) cSCC. Two-year disease-free survival was 62% and decreased to 47% at 5 years. Parotid involvement, positive margins, nodal metastasis, or the presence of perineural invasion did not correlate with decreased survival (P>.05). Distant metastasis was a strong indicator of poor overall survival (P<.001). Adjuvant postoperative radiotherapy did not improve overall survival (P=.42). Overall survival was poor for patients with advanced recurrent cSCC despite the combined treatment with surgery and radiotherapy.